ANALISIS HISTORIS TRADISI STUDI ISLAM DI JERMAN Telaah atas Karya Josef van Ess - Umi Sumbulah (Litbang STFT Widya Sasana Malang, 2007)
Study of Islam in Germany started from an approach of purely clasical philology. Such approach has been done by analyzing historical and traditional islamic texts as Wellhausen and Noldeke did. Considering some weakness of this approach, new perspective is put forward. This new one is called philological approach “plus”. The advantage of this new approach is that islamic texts are analyzed not only in philological but also sociological point of view. Such analysis has been done by Becker who can be called as pioneer of new study of Islam in Germany. This article is my study on the book of Josef van Ess, From Wellhausen to Becker: The Emergence of Kulturgeschichte in Islamic Studies, who critically views Becker as one of the leading studious person on Islam with new perspectives